Enteric Encephalopathy associated with reversible ECG changes: A Diagnostic Dilemma - Somnath Maitra; Sk Adnan Yusuf; Koushik Ray (International Journal of Medical Research and Review, 2022)
Enteric fever is common in India. It presents with various clinical manifestations. Encephalopathyand ECG changes are indicators of prognosis. Persistent ECG changes indicate a poor prognosis. Thepathogenesis of encephalopathy is unclear though prostaglandins and free oxygen species may beimplicated in the prognosis and justifies the use of steroids in enteric encephalopathy withantibiotics. The case presented here presented with encephalopathy and ECG changes whichreversed following antibiotic and steroid therapy. The importance of the case lies in the fact thattyphoid should not be missed in the diagnosis of encephalopathy and ECG should be done in allcases of enteric fever to determine the prognosis.